A naphthalimide-based solid state luminescent probe for ratiometric detection of aluminum ions: in vitro and in vivo applications. Issue 94 (10th November 2017) - Gupta, Neha; Kaur, Taranjeet; Bhalla, Vandana; Parihar, Ripu D.; Ohri, Puja; Kaur, Gurcharan; Kumar, Manoj
Abstract : A naphthalimide-based solid state luminescent probe has been designed and synthesized for the detection of Al 3+ ions in solution as well as in the solid state with its versatile applications as materials and as a bio-imaging tool for the detection of Al 3+ ions under in vitro and in vivo milieu. Abstract : A naphthalimide-based fluorescent probe 4 has been designed and synthesized that detects Al 3+ ions in solution, solid state and in biological systems, including cells, tissues and nematodes. Further, a portable kit has been developed using probe 4 for the on-site detection of Al 3+ ions.